Variasi suhu pengeringan dan pengaruhnya terhadap karakteristik mutu fungsional bubuk mangga gedong gincu - Devry Pramesti Putri; Wawan Agustina; Ainia Herminiati; Raden C.E. Andriansyah; Siti Khudaifany DFAP; Achmat Sarifudin (AGROINTEK, 2022)
Mango, including the type of Gedong gincu, is a seasonal fruit. This condition causes the number to be abundant during the harvest season but will become scarce in the months afterward. Efforts to increase the economic value, shelf life, and use of mangoes that are not acceptable to the market in the form of fresh fruit, can be done through product diversification in processed form. One alternative that can be done is to make dried gincu gedong mango powder which can be used as an intermediate product. The purpose of this study was to study the effect of heating temperature (steam temperature, drying temperature of 40, 50, 60 and 70 oC) on the quality of steamed mango puree and gedong gincu mango powder on several parameters: color, moisture content, ash content, vitamin C, beta-carotene and antioxidant activity (IC50). The results showed that the heating temperature increased the yellowish color and brightness of the mango powder. Increasing the drying temperature decreased the moisture content but increased the ash content of mango powder. The drying temperature that produces antioxidant activity (IC50) and the highest vitamin C content is 70oC. The drying temperature that produces the highest beta-carotene content is 60 oC.